System Level modelling of fuel cell driven electric vehicles - Codina, Albert Cerdán (My University, 2017)
Nowadays, climate change is an issue of major concern for the majority of the world’s society. Not just the emission of Greenhouse Gases but also the brutal pace at which fossil fuels are being consumed. Within that topic and having innovation in mind, several alternatives have risen in the automotive industry in order to address this issue such as Battery Electric Vehicles or more recently at a commercial scale, Fuel Cell Vehicles. This last technology uses hydrogen as a fuel and transforms the chemical energy generated in the reaction with oxygen in electricity able to drive an electric motor, usually a PMSM. This report will try to take an insight in this technology using different approaches. To do so, literature work will be done in order to review Hydrogen production, transportation and storage and how is now positioned as an energy resource in the world. Moreover, fuel cell technologies will be reviewed and explained as well as compared. Also, some literature work will be done in order to explain how a fuel cell vehicle operates and which are the most important elements of its drivetrain, also evaluating cost and feasibility of this kind of automotive solution. Having reviewed the current state of the art of fuel cell technologies, this report will explain how the electric drivetrain of a fuel cell vehicle can be modelled in a Simulation platform such as MATLAB/Simulink. The most important elements of the fuel cell vehicle drivetrain will be modelled (Fuel cell stack, boost converter, power systems, etc.) and will be tested to see how they behave on its own and as a part of a small vehicle fuel cell drivetrain. With the obtained results several conclusions were extracted as well as some future work pathways such as adapting the small scale model to a full power commercial vehicle model. In all, this report will try to make clear how fuel cell vehicles can be considered as a feasible alternative to substitute conventional mobility methods.
Keywords: Elkraftteknik; Electric power engineering